2016
DOI: 10.1186/s12872-016-0274-7
|View full text |Cite
|
Sign up to set email alerts
|

Two parameters reflect lipid-driven inflammatory state in acute coronary syndrome: atherogenic index of plasma, neutrophil–lymphocyte ratio

Abstract: BackgroundAtherosclerosis is a systemic, lipid-driven immune-inflammatory disease.MethodsWe retrospectively reviewed institutional electronic medical records to seek chest pain patients who were suspicious of acute coronary syndrome (ACS) between January 2011 and December 2013. All the patients were identified by undergoing coronary angiography. On admission white blood cell and its subtypes were measured as part of the automated complete blood count and fasting venous blood samples were obtained and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…These data indicated that IL-8 level is affected by intensity of exercise. The present study detected significant increase in atherogenic index in both obese non-ovx and obese ovx subgroup versus lean subgroup, these results also comes in agreement with other several studies, As Pourfarzam, et al [63] ; Zhan et al [64] ; Gaojun Cai et al [65] ; Shen et al [66] demonstrated that atherogenic index associated with metabolic syndrome and it was higher in coronary heart diseases. Furthermore it was positively correlated with TC, TG and negatively correlated with HDL-C.…”
Section: Discussionsupporting
confidence: 93%
“…These data indicated that IL-8 level is affected by intensity of exercise. The present study detected significant increase in atherogenic index in both obese non-ovx and obese ovx subgroup versus lean subgroup, these results also comes in agreement with other several studies, As Pourfarzam, et al [63] ; Zhan et al [64] ; Gaojun Cai et al [65] ; Shen et al [66] demonstrated that atherogenic index associated with metabolic syndrome and it was higher in coronary heart diseases. Furthermore it was positively correlated with TC, TG and negatively correlated with HDL-C.…”
Section: Discussionsupporting
confidence: 93%
“…When taking into account the fact that there is a significant relationship between these two risk scoring systems and N/L ratios and N/L ratio is higher in patients with higher troponin levels, this supports other literature information and considerations of important authors about N/L ratio can be used as a practical risk marker in ACS. In a study of Zhan et al, N/L ratio was found highest in the STEMI group among the ACS subgroups [28].…”
Section: Discussionmentioning
confidence: 89%
“…There are studies in which the TG and HDL and the ratio of TG and HDL can be used to calculate the PAI. Zhan et al [19] showed that PAI levels were higher in acute coronary syndrome patients compared to controls. Niroumand et al [7] determined that PAI can be used as an indicator of the cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%